2020
DOI: 10.1111/1751-7915.13598
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites from plant‐associated Pseudomonas are overproduced in biofilm

Abstract: Plant rhizosphere soil houses complex microbial communities in which microorganisms are often involved in intraspecies as well as interspecies and inter-kingdom signalling networks. Some members of these networks can improve plant health thanks to an important diversity of bioactive secondary metabolites. In this competitive environment, the ability to form biofilms may provide major advantages to microorganisms. With the aim of highlighting the impact of bacterial lifestyle on secondary metabolites production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 84 publications
1
54
0
2
Order By: Relevance
“…Moreover, apart from these bacterial secondary metabolites known to be involved in plant–bacteria interactions, two newly described families of secondary metabolites were significantly accumulated in F113 in response to root extracts. On one hand, the production of two pyridine-2,6-thiocarboxylic derivatives (PDTC) m/z 198 and m/z 228 [ 28 ] was increased in response to plant extracts; for example, the m/z 198 compound was 930-, 927- and 358-fold overproduced in the presence of Adular, Bordeaux and Soissons extracts, respectively ( Figure 3 ). On the other hand, the production of three atypical compounds described as acyl-dihydro-methyl-pyrrol derivatives [ 28 ], was also strongly influenced by root extracts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, apart from these bacterial secondary metabolites known to be involved in plant–bacteria interactions, two newly described families of secondary metabolites were significantly accumulated in F113 in response to root extracts. On one hand, the production of two pyridine-2,6-thiocarboxylic derivatives (PDTC) m/z 198 and m/z 228 [ 28 ] was increased in response to plant extracts; for example, the m/z 198 compound was 930-, 927- and 358-fold overproduced in the presence of Adular, Bordeaux and Soissons extracts, respectively ( Figure 3 ). On the other hand, the production of three atypical compounds described as acyl-dihydro-methyl-pyrrol derivatives [ 28 ], was also strongly influenced by root extracts.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the production of two pyridine-2,6-thiocarboxylic derivatives (PDTC) m/z 198 and m/z 228 [ 28 ] was increased in response to plant extracts; for example, the m/z 198 compound was 930-, 927- and 358-fold overproduced in the presence of Adular, Bordeaux and Soissons extracts, respectively ( Figure 3 ). On the other hand, the production of three atypical compounds described as acyl-dihydro-methyl-pyrrol derivatives [ 28 ], was also strongly influenced by root extracts. The derivative whose synthesis was mostly affected was the m/z 280 compound, with a 46-, 29- and 44-fold overproduction in the presence of Adular, Bordeaux and Soissons extracts, respectively ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study we found that different growth media inflicted variations in the resulting interaction between Bacillus subtilis and Pseudomonas chlororaphis 15 . The two strains come into close contact in lysogeny broth (LB) medium, while in King's B medium, which promotes the production of secondary metabolites by Pseudomonas strains 24 , the two colonies were physically separated by a typical inhibition halo (Suppl. Figure 1a).…”
Section: The Interaction Between Pcl and Bamy Progresses From Antagonmentioning
confidence: 99%